Late Paleozoic tectono-sedimentary evolution of eastern Chaco-Paraná Basin (Uruguay, Brazil, Argentina and Paraguay) - Veroslavsky, Gerardo; Rossello, Eduardo A.; López-Gamundí, Oscar; de Santa Ana, Héctor; Assine, Mario L. [UNESP]; Marmisolle, Josefina; de J Perinotto, Alexandre [UNESP] (Elsevier, 2021)
Recent surface and subsurface information from the Chaco-Paraná Basin in Argentina, Brazil, Paraguay and Uruguay south of the Asunción Rio Grande Arch allowed proposing a regional tectonic-sedimentary evolution for the Late Paleozoic megasequences. A new stratigraphic column for the Chaco-Paraná Basin is proposed based on the integration of outcrop and well data and 2D seismic surveys. We present updated isopach maps of each of the megasequences. The basin fill can be divided into three megasequences: Devonian (Pragian-Emsian), Late Carboniferous, and Permian (Asselian-Wuchiapingian). These megasequences were deposited under similar paleogeographic conditions, with predominantly marine siliciclastic sedimentation. The provenance areas were located to the east, while the marine domain was located to the west. The Devonian megasequence (~300 m total thickness) is subdivided into three units: the Cerrezuelo, Cordobés and La Paloma formations. Its presence had only been confirmed in the southern region of the study area, but new geophysical data suggest its extension into the western sector. The Late Carboniferous megasequence consists of fluvial and glaciomarine rocks, and includes the San Gregorio and Cerro Pelado formations in Uruguay, and the coeval Itararé Group in Brazil. These units thicken towards the west, where they reach up to 250 m. The Permian megasequence (~1200 m total thickness) is composed, from base to top, of the Tres Islas, Fraile Muerto, Mangrullo, Paso Aguiar, Yaguarí and Buena Vista formations, and correlatable units in the Brazilian sector of the Paraná Basin. Both Devonian and Permian sedimentary successions include marine black shales with high organic matter content. These shales are considered regional potential hydrocarbon sources. The provenance areas of the basin are the Proterozoic and Neoproterozoic-Cambrian basement, associated with the Plata High to the south and the Dom Feliciano High to the east and north, respectively. The basement configuration strongly influenced the distribution, thickness and lithological characteristics of the Late Paleozoic megasequence, as well as the connection between the Chaco-Paraná and Paraná basins. A NNE-SSW fault-bounded depocenter, here named the Central Paranaense Trough, is a remarkable tectonic feature 600 km long, bounded by the NE-SW Lancinha, Taxaquara and Jacutinga dextral strike slip fault zones in the Paraná Basin.
Keywords: Argentina; Brazil; Chaco-Paraná basin; Late Paleozoic; Paraguay; Tectonic -sedimentary evolution; Unconformity-bounded megasequences; Uruguay